Postoperative Continence Assessment in Female Patients with Anorectal Malformations: A Tertiary Care Center Study - Anjana Kaza; K. T. Mandakini; Bhuvaneshwar Rao (Journal of Indian Association of Pediatric Surgeons)
Background: Anorectal malformations (ARMs) include a group of congenital anomalies affecting the distal anorectum with frequent involvement of the urogenital tract. As modern surgical advancements have improved survival, attention has shifted toward assessment and optimization of bowel function, to improve the overall quality of life for affected children. Objective: The objective of this study was to evaluate the bowel functional outcomes for individual types of female ARMs after standardized management at a tertiary center. Materials and Methods: The present study included 35 female patients with anorectal malformations aged >3 years, who underwent single staged/staged ARM repair, and finished dilatation program. Patient demographics, type of ARM, surgeries performed, and postoperative complications were noted. Bowel function was assessed using the Krickenbeck scoring system for postoperative results. Those with continence issues underwent contrast enema and magnetic resonance imaging (MRI) pelvis. Results: The study included 24 patients with vestibular fistula, 7 with perineal fistula, 2 with rectovaginal fistula, and 2 with perineal canal. Voluntary bowel movement (VBM) was achieved in 34 (97.15%) patients post-ARM repair, constipation in 8 (22.85%) patients, and soiling in 2 (5.7%) patients. Of these, 3 patients had abnormal findings on contrast enema and 2 on MRI pelvis. Conclusion: VBM was achieved by majority of the females following ARM repair. Constipation was the most common functional complication. Soiling noted in 2 cases was due to overflow incontinence secondary to constipation. Early initiation of targeted bowel management showed improvement in affected subjects. The Krickenbeck scoring system for postoperative results is a quick, easy method of identifying patients with functional incontinence based on symptoms.